Two new genera and one new species of Pantheinae from East Asia (Lepidoptera, Noctuidae: Pantheinae). Revision of Pantheinae, contribution XI - Behounek, G.; Han, H.l.; Kononenko, V.s. (Zootaxa, 2015)
Two new genera, Pantheaforma gen. n. (Type-species Pantheaforma ihlei sp. n.) and Chrisotea gen. n. (Type-species Trichosea zhangi Chen, 1990) from East Asia and a new species Pantheaforma ihlei sp. n. from Thailand and Myanmar are described. New combination Chrisotea zhangi (Chen, 1990), comb. n. is proposed. New taxa are illustrated with imagines in colour and male and female genitalia. The little-known species Pantheana yangzisherpana Hreblay, 1998, formerly only known from Nepal is reported for China for the first time.